Business model analysis for music and healthcare sectors: designing frameworks to provide music therapy services to children with developmental disabilities in Klang Valley / Siti Nur Ain Amiruddin - Amiruddin, Siti Nur Ain (2022)
This research aims to investigate business model analysis in the music and healthcare sectors, with the goal of developing frameworks for providing music therapy services to children with developmental disabilities in Klang Valley. It's a qualitative exploratory study aimed at describing the process of music therapy as it's utilised in the recovery of children with developmental impairments, as well as its perceived usefulness and success, as well as the restrictions and restraints that local practitioners frequently confront. The findings of this study will be valuable to local mental health experts, such as school counsellors, who may want to employ art therapy to help children with developmental difficulties heal. A type of qualitative research, was used in this study. Interviews with music therapists about the role of songs with their adult clients with developmental impairments were transcribed and analysed as part of the process. I believe that the lives of people with developmental impairments are no less complicated than those of those who are usually developing. The example will be based on a specific publication or article that has been identified as relevant to the study goal. In addition, few different sources, such as books, papers, the internet, and the media, align with subjective exploration strategies where it will be proposed to choose the best end for flow research point. To summarise, music therapy is a relatively young field in Malaysia, and steps must be taken to enhance it and increase public awareness of its benefits. There are also some recommendations for future research in order to generate additional literature regarding music therapy, particularly in relation to its practise in Malaysia.